Ideal Teachers’ Personalities Motivating English Learners in Senior High School - Abd Halim; Nur Mutmainna Halim; Dewi Sartina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The objectives of the research are 1) to outline the ideal teachers’ personalities as perceived by students; 2) to describe students' motivation in learning English taught by teachers who have these ideal teachers' personalities; and 3) to construe the impact on students' perceptions of the teachers' personalities with their motivation. This research was designed by applying descriptive methods with quantitative approaches. The study participants were 149 students and four teachers from MAN 1 Makassar. They were chosen by random cluster technique. The data were obtained through questionnaires, interviews, and observation. The result of the findings showed that the ideal teachers' personalities as perceived by students are friendly (93.95%), followed by sincere (93.29%), polite (93.28%), patient (92, 62%), good teaching skill/ability (91,95%), organized (89,27%), care/ empathetic (83,89%), cheerful (83,21%), creative (81,88%) and attractive (81,21%), patient (75%), and cheerful (75%). The findings also show that most students who learn English are motivated by the ideal teachers' personalities. Students tend to be more motivated in learning if teachers have positive behavior and characteristics such as being friendly, organized, cheerful, creative, patient, and having good teaching skills/abilities. This research showed that teachers with good personalities would quickly build relationships with students to improve their motivation to learn. The findings also showed a significant correlation between teachers' personalities and students' motivation to learn English. Keywords: Student's Learning Motivation, Teacher's Personality